Evaluation of symptomatic slow-acting drugs in osteoarthritis using the GRADE system - Bruyère, O; Burlet, N; Delmas, P; Rizzoli, R; Cooper, C; Reginster, J (BioMed Central, 2008)
Background: Symptomatic slow-acting drugs (SYSADOA) have been largely studied over the last decade. The objective of this study is to prepare a document providing recommendations for the use of SYSADOA in osteoarthritis (OA). Methods: The following interventions were taken into consideration: avocado/soybean unsaponifiables, chondroitin sulfate, diacereine, glucosamine sulfate, hyaluronic acid, oral calcitonin, risedronate, strontium ranelate. Recommendations were based on the GRADE (Grading of Recommendations Assessment, Development and Evaluation) system. The GRADE system is based on a sequential assessment of the quality of evidence, followed by assessment of the balance between benefits versus downsides and subsequent judgment about the strength of recommendations. Results: Chondroitin sulfate, diacereine, glucosamine sulfate, avocado/soybean unsaponifiables and hyaluronic acid have demonstrated pain reduction and physical function improvement with very low toxicity, with moderate to high quality evidence. Even if pre-clinical data and some preliminary in vivo studies have suggested that oral calcitonin and strontium ranelate could be of potential interest in OA, additional well-designed studies are needed. Conclusion: In the benefit/risk ratio, the use of chondroitin sulfate, diacereine, glucosamine sulfate, avocado/soybean unsaponifiables and hyaluronic acid could be of potential interest for the symptomatic management of OA.